Moodle-Based E-learning Development by Implementing Gamification Concept - Landebila, Jumiatin; Saputra, Hendra Nelva; Razilu, Zila (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to produce moodle-based e-learning media by applying the concept of gamification to the subject